2022
DOI: 10.1071/cp22255
|View full text |Cite
|
Sign up to set email alerts
|

Seed priming and soil application of zinc decrease grain cadmium accumulation in standard and zinc-biofortified wheat cultivars

Abstract: Context Cadmium (Cd) is a toxic metal for both plants and humans. Wheat grown on Cd-contaminated soils may accumulate toxic levels of Cd in grains. Aim This study aimed to compare soil zinc (Zn) application and seed Zn-priming for decreasing grain Cd concentration in standard and Zn-biofortified wheat cultivars grown on Cd-spiked soil. Methods Standard (Jauhar-2016) and Zn-biofortified (Zincol-2016) wheat cultivars were grown in pots filled with Cd-spiked soil (8 mg Cd kg−1). The tested Zn treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…While the priming treatment is administered for only a brief period during the early stages of seed germination, its impacts can endure throughout the entire lifespan of the plant . Indeed, researchers have reported that priming wheat seeds with zinc ions or zinc oxide nanoparticles can effectively decrease the accumulation of Cd in grains grown in Cd-contaminated alkaline fields. , However, the molecular and metabolic mechanisms associated with seed priming remain poorly understood . Generally, the absorption of Cd by roots is facilitated through the transporters or channels that have evolved to absorb essential metals such as copper (Cu), iron (Fe), zinc (Zn), and manganese (Mn) .…”
Section: Introductionmentioning
confidence: 99%
“…While the priming treatment is administered for only a brief period during the early stages of seed germination, its impacts can endure throughout the entire lifespan of the plant . Indeed, researchers have reported that priming wheat seeds with zinc ions or zinc oxide nanoparticles can effectively decrease the accumulation of Cd in grains grown in Cd-contaminated alkaline fields. , However, the molecular and metabolic mechanisms associated with seed priming remain poorly understood . Generally, the absorption of Cd by roots is facilitated through the transporters or channels that have evolved to absorb essential metals such as copper (Cu), iron (Fe), zinc (Zn), and manganese (Mn) .…”
Section: Introductionmentioning
confidence: 99%